Impact of Coronavirus Disease 2019 (COVID-19) Outbreak on Acute Admissions at the Emergency and Cardiology Departments Across Europe - Sokolski, Mateusz (Am J Med, 2021)
PURPOSE: We evaluated whether the severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) pandemic was associated with changes in the pattern of acute cardiovascular admissions across European centers. METHODS: We set-up a multicenter, multinational, pan-European observational registry in 15 centers from 12 countries. All consecutive acute admissions to emergency departments and cardiology departments throughout a 1-month period during the COVID-19 outbreak were compared with an equivalent 1-month period in 2019. The acute admissions to cardiology departments were classified into 5 major categories: acute coronary syndrome, acute heart failure, arrhythmia, pulmonary embolism, and other. RESULTS: Data from 54,331 patients were collected and analyzed. Nine centers provided data on acute admissions to emergency departments comprising 50,384 patients: 20,226 in 2020 compared with 30,158 in 2019 (incidence rate ratio [IRR] with 95% confidence interval [95%CI]: 0.66 [0.58-0.76]). The risk of death at the emergency departments was higher in 2020 compared to 2019 (odds ratio [OR] with 95% CI: 4.1 [3.0-5.8], P < 0.0001). All 15 centers provided data on acute cardiology departments admissions: 3007 patients in 2020 and 4452 in 2019; IRR (95% CI): 0.68 (0.64-0.71). In 2020, there were fewer admissions with IRR (95% CI): acute coronary syndrome: 0.68 (0.63-0.73); acute heart failure: 0.65 (0.58-0.74); arrhythmia: 0.66 (0.60-0.72); and other: 0.68(0.62-0.76). We found a relatively higher percentage of pulmonary embolism admissions in 2020: odds ratio (95% CI): 1.5 (1.1-2.1), P = 0.02. Among patients with acute coronary syndrome, there were fewer admissions with unstable angina: 0.79 (0.66-0.94); non-ST segment elevation myocardial infarction: 0.56 (0.50-0.64); and ST-segment elevation myocardial infarction: 0.78 (0.68-0.89). CONCLUSION: In the European centers during the COVID-19 outbreak, there were fewer acute cardiovascular admissions. Also, fewer patients were admitted to the emergency departments with 4 times higher death risk at the emergency departments.